2019
DOI: 10.18632/aging.102165
|View full text |Cite|
|
Sign up to set email alerts
|

The combination of lonafarnib and sorafenib induces cyclin D1 degradation via ATG3-mediated autophagic flux in hepatocellular carcinoma cells

Abstract: Combination treatment is a promising strategy to improve prognosis of hepatocellular carcinoma (HCC). Sorafenib is a traditional first-line agent approved for the treatment of advanced HCC, though with limited efficacy. Previously, we reported that lonafarnib, an orally bioavailable non-peptide inhibitor targeting farnesyltransferase, synergizes with sorafenib against the growth of HCC cells. In the present study, we aim to clarify the underlying mechanism of this combination strategy. Initially, using in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Every year, the government has provided millions of money to the studies of HCC, and sorafenib and regorafenib have made great contributions for the therapy of HCC. What's more, many studies have focused the mechanisms of HCC progression and metastasis [26][27][28][29]. Our study based on the clinical samples databases, and identified a new pathway connected to the progression of HCC, is another sample to study HCC progression for better therapy of HCC patients.…”
Section: Discussionmentioning
confidence: 93%
“…Every year, the government has provided millions of money to the studies of HCC, and sorafenib and regorafenib have made great contributions for the therapy of HCC. What's more, many studies have focused the mechanisms of HCC progression and metastasis [26][27][28][29]. Our study based on the clinical samples databases, and identified a new pathway connected to the progression of HCC, is another sample to study HCC progression for better therapy of HCC patients.…”
Section: Discussionmentioning
confidence: 93%
“…In HCC, it was shown that the molecular mechanisms by which sorafenib induces autophagy could be independent of AMP-activated protein kinase (AMPK) and involve a reduction in MCL-1 levels, which in turns would inactivate signal transducer and activator of transcription 3 factor (STAT3), causing the accumulation of beclin-1 (BECN-1) and other proteins indicating autophagosome formation, such as LC3B-II accumulation, as well as sequestosome 1 (p62) reduction [25,28,41,49,73]. Several studies reported a dosedependent cytotoxic effect of sorafenib, along with the induction of the assembly of the autophagolysosome, which was accompanied by reduced cell viability and an increase in annexinV/Pi-positive cells in vitro, as well as by an increase in LC3-II conversion and autophagosome formation in tumor samples and a reduced tumor burden in HCC-bearing mice [37,41,74].…”
Section: Cell Death Mechanisms Related To Sorafenibmentioning
confidence: 99%
“…We analyzed the correlation between APEX1expression and drug resistance in HCC patients. Sorafenib is the gold standard main chemotherapeutic drug for treating advanced stage HCC patients, but its efficacy is affected by drug resistance [28]. We evaluated the correlation between APEX1 and sorafenib-resistance in HCC patients from the GSE109211 database.…”
Section: High Apex1 Expression Correlates With Drug Resistance In Hccmentioning
confidence: 99%
“…reported in the United States [32]. Sorafenib is the only FDA-approved chemotherapeutic drug for advanced stage HCC [28]. There is an urgent need for novel therapeutic options for HCC to overcome the poor survival outcomes because of fewer effective drugs, chemotherapeutic resistance, and radiation toxicity.…”
Section: Agingmentioning
confidence: 99%